60 lat borykania się z brakiem tożsamości - Balint, Lea (Zagłada Żydów. Studia i Materiały, 2011)
The article deals with the phenomenon of “children without identity,” i.e. children rescued from the Holocaust born in Poland during 1936–1945 who lost both their parents. They can be divided into two groups: the saved ones who lost their identity during the war or right afterwards (of whose past we know nothing; sometimes the only piece of information is the name given to them by the Poles during the war) and the saved ones whose identity was lost during the process of emigration (children who remembered their names and could talk about their parents and their past at the end of the war, but who forgot everything later on). The author discusses the condition of the archive materials about “children without identity” and about their lot: about the ways of adaptation in Israel and Poland, traumas, reasons for not speaking about their identity loss and the search for their past.